Peran Guru Ismuba dalam Membentuk Akhlak Islami Pelajar SMP Muhammadiyah 2 Depok - Ganjar Rachmawan Adiprana; Hendro Widodo (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2020)
Junior high school students in the study of developmental psychology enter the stages of adolescence, which means a foothold to reach the stage of becoming an adult. A teenager will experience puberty or a period of searching for his identity because in his mind there is a conflict of values between those learned in the family, community, school, to friends. Islamic education institutions are certainly expected to be able to give a bright color in the form of a good influence on the development of adolescent students through learning in the classroom and outside the classroom which leads to the formation of Islamic morals. An effective way to shape students' Islamic morals is through habituation. This research is a qualitative type with data collection method through interviews and direct observations in the research field, namely Muhammadiyah 2 Junior High School, Depok, Sleman, Yogyakarta. This school has a vision of education with morality, education, achievement and environmental insight. Muhammadiyah 2 Junior High School Depok as one of the Islamic educational institutions assigns tasks to Ismuba Teachers (Al-Islam, Kemuhammadiyahan, and Arabic) specifically as the frontline in organizing, running, and evaluating programs that are related to shaping Islamic student morals with Employee Teachers and all school residents in general.